Implementasi Kurikulum Merdeka Dalam Melestarikan Budaya Nusantara - Rudi Hartono; I Wayan Suastra; I Wayan Lasmawan (LP. Ma'arif Janggan Magetan, 2023)
The independent curriculum is a learning method that refers to the talent and interest approach. Students can choose what subjects they want to learn according to their passion. This independent curriculum, the government makes every effort to take advantage of the role of digital in the education system in Indonesia, as evidenced by the existence of platforms that support the learning process. This means that teachers are required to be able to optimize existing digital to add insight and knowledge about learning. The implementation of the independent curriculum is carried out to build and preserve the culture of the Archipelago through the Strengthening the Profile of the Pancasila Student Project. This research was conducted using a descriptive qualitative method which was carried out on students of SDN Slipi 15. In this art performance activity, the dances performed by the students were as follows: (1) Saman dance from Aceh; (2) the Betawi flower creation dance; (3) Kreasi Rampak Warrior Dance from Central Java; (4) Amko rambe yamko dance; (5) Betawi martial arts; (6) Dance created by bells from Kalimantan; (7) Dance created by Alusia from North Sumatra; (8) Manuk dadali dance from West Java; (9) Ondel-ondel dance from Jakarta.